Institutional Analysis Of The Farmers Association Of Community Forest Management In Sekampung Upper Watershed (Case Studies On Gapoktan Hijau Makmur) - Zainal Mutaqin (Jurnal Ilmiah ESAI, 2013)
To study the performance of Gapoktan Hijau Makmur as the farmers association of community forest management has been done analysis of Gapoktan institutions. The results of research showed that the: (1) Changes in institutions which followed with the application of cultivation technology crop and agriculture conservation system  will improve the performance of the group and it's better than its original state, and (2) on working area which does not have the natural obstacles (natural barrier) and it is not a great problem about  distances  place that far apart (social distance), then the form of  large institutions  is the most appropriate; whereas on working area who has a natural obstacles (natural barrier),  the form of small institutions (sub group -sub group) with the application of regulations which assertive and strong for members of the group, and  decision mechanisms  of organization through sub group-sub groups is an appropriate  institutional form . Key words: Institutions, and performance, community, forest